Glycaemic, gastrointestinal and appetite responses to breakfast porridges from ancient cereal grains: a MRI pilot study in healthy humans - Alyami, Jaber; Ladd, Nidhi; Pritchard, Susan E.; Hoad, Caroline L.; Abdul Sultan, Alyshah; Spiller, Robin C.; Gowland, Penny A.; MacDonald, Ian A.; Aithal, Guruprasad P.; Marciani, Luca; Taylor, Moira A. (Elsevier, 2017)
Cereal grain based porridges are commonly consumed throughout the world. Whilst some data are available for varieties that are popular in the Western world such as oats and rye, other ‘ancient’ grains used in the East and in Africa such as millets are thought to have beneficial health effects, such as a suppression of post prandial hunger and circulating glucose levels. These grains, a sustainable food source due to their tolerance of extreme weather and growing conditions, are commonly found throughout Asia and Africa. However, knowledge of the physiological responses to these grain varieties is very limited. This study aimed to collect initial pilot data on the physiological and gastrointestinal responses to breakfast porridges made with two millet varieties and oats and rye grains. A total of n = 15 completed the oats and rye, n = 9 the finger millet n = 12 the pearl millet meals. MRI scans were undertaken at baseline, immediately after consumption and then hourly postprandially. Blood glucose was measured at baseline, immediately after consumption and then every 15 min until t = 80 min, then every 20 min until t = 120 min, followed on each occasion by completion of VAS. Seven participants completed the entire protocol and were included in the final analysis. A subgroup analysis with the n = 10 paired comparison between the same individuals that completed the oats, rye and pearl millet was also considered. The gastric volume AUC was higher for pearl millet than oats and rye (n = 10, p<0.001). The incremental area under the curve (iAUC) for blood glucose was not significantly different between the meals although this showed a trend to be lower for pearl millet. Hunger was lower for pearl millet compared to oats and rye (n = 10, p = 0.01). There was a significant correlation between total gastric volume AUC and average appetite AUC r = -0.47, p < 0.010. Isoenergetic breakfast porridges from ‘ancient’ varieties of millet grains showed physiological responses that were comparable with those from common Western varieties known to have beneficial health effects. Pearl millet appeared to induce lower postprandial blood glucose response and appetite scores though the differences were not conclusive compared with the other porridges and further work is needed. Improved knowledge of the effects of different cereal grains could help direct dietary advice and ultimately improve health outcomes in the general population worldwide.